Phytochemicals in Breast Cancer Prevention and Therapy: Mechanisms, Efficacy, and Future Prospects - Neha Kodali; Chikezie O. Madu; Yi Lu (Current Issues in Molecular Biology)
Breast cancer is one of the most common forms of cancer in women globally. Phytochemicals are naturally occurring compounds in plants that have been the focus of many research studies for their potential in cancer prevention and treatment. This review will explore the mechanisms certain phytochemicals use to interact with the cellular pathways involved in breast cancer development. Phytochemicals modulate various processes such as apoptosis, cell cycle regulation, angiogenesis, and metastasis to potentially combat breast cancer. This review will also examine different dietary sources of phytochemicals, the potential for integration of phytochemicals into breast cancer therapy, the safety, toxicity, and limitations of phytochemicals, and the future of phytochemicals in the context of breast cancer.